Relationship Between Anxiety Level and Sleep Quality in Patients Pre-Cardiac Surgery at Dr. Kariadi Hospital, Semarang, Indonesia - Santoso, Teguh; Junait; Fatmawati, Endang (Babali Publisher, 2024)
Introduction: Cardiac surgery is a medical procedure that aims to improve the heart's structure and blood vessels. The procedure is performed within 4 to 6 hours. This can cause anxiety in patients and family members. Excessive anxiety can lead to increased blood pressure, tachycardia, depression, and even sleep disturbances before and after cardiac surgery. Poor sleep quality affects quality of life, health status, and activities of daily living. The aim of this study was to determine the relationship between anxiety levels and sleep quality in patients with pre-cardiac surgery. Methods: This research was a descriptive correlation with a cross-sectional approach. The convenience sampling technique was used to select 65 respondents for the sample. The Hamilton Anxiety Rating Scale (HARS) questionnaire was used to gather information on anxiety levels. The Pittsburgh Sleep Quality Index (PSQI) questionnaire assessed the respondents' sleep quality before heart surgery. The obtained data was subjected to analysis using the Spearman-Rho test.Results: There were 36 respondents (55.38%) who had moderate sleep quality and experienced mild anxiety 28 respondents (43.08%). The Spearman rho correlation test of r value was 0.106 in the results. There is no relationship between anxiety level and sleep quality in cardiac pre-surgery patients.Conclusion: The majority of patients with pre-cardiac surgery at Dr. Kariadi Hospital Semarang experience anxiety and sleep disorders. Nurses can consider to manage the anxiety and sleep disorders experienced by patients.